2019
DOI: 10.1016/j.neubiorev.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Social perceptual function in parkinson’s disease: A meta-analysis

Abstract: Highlights  Parkinson's disease is associated with significant social perceptual impairment. The magnitude of this impairment is broadly equivalent across facial and prosodic modalities. Social perceptual impairment is evident for all six basic emotions, but is generally greater for negatively valanced emotions. Both dopaminergic medication and subthalamic nucleus deep brain stimulation are associated with poorer social perceptual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 94 publications
5
47
0
Order By: Relevance
“…The characteristics of studies assessing FER in PD patients undergone STN DBS are summarized in Table 1 . In the recent meta-analysis of Coundouris et al [ 56 ] examining social perceptual function in PD, the subanalysis concerning DBS showed that PD patients were significantly impaired in perception functions after STN DBS surgery from either facial or vocal stimuli compared to matched healthy controls (HC). The majority of studies included PD patients eligible for DBS according to standard inclusion and exclusion criteria [ 57 ], i.e., patients with idiopathic PD and severe motor disability, clear response to levodopa, occurrence of disabling levodopa-related motor complications and absence of dementia, significant neuropsychiatric disorders, and abnormalities on brain MRI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of studies assessing FER in PD patients undergone STN DBS are summarized in Table 1 . In the recent meta-analysis of Coundouris et al [ 56 ] examining social perceptual function in PD, the subanalysis concerning DBS showed that PD patients were significantly impaired in perception functions after STN DBS surgery from either facial or vocal stimuli compared to matched healthy controls (HC). The majority of studies included PD patients eligible for DBS according to standard inclusion and exclusion criteria [ 57 ], i.e., patients with idiopathic PD and severe motor disability, clear response to levodopa, occurrence of disabling levodopa-related motor complications and absence of dementia, significant neuropsychiatric disorders, and abnormalities on brain MRI.…”
Section: Resultsmentioning
confidence: 99%
“…Another issue is whether PD patients with normal FER performance before and deficit after DBS actually had a subtle FER deficit before DBS being revealed after surgery. Indeed, PD patients exhibit significant social perceptual deficits including FER impairment [ 56 , 76 ]. Areas involved in the process of recognizing emotions in faces such as the amygdala, basal ganglia, insula, the orbitofrontal, and anterior cingulate cortex are affected by PD-related pathology [ 77 ].…”
Section: Discrepancies Between Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As this resulted in mean effects not being independent, these subcategories were not compared statistically. Instead, to interpret differences between mean effect sizes, differences in effect size magnitude, as well as the percentage of variance accounted for (PVAF) by having a diagnosis of AD versus being a control participant was referred to (see, Adams et al, 2019;Coundouris et al, 2019).…”
Section: Data Extractionmentioning
confidence: 99%